If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 81 = 3n Solving 81 = 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 81 + -3n = 3n + -3n Combine like terms: 3n + -3n = 0 81 + -3n = 0 Add '-81' to each side of the equation. 81 + -81 + -3n = 0 + -81 Combine like terms: 81 + -81 = 0 0 + -3n = 0 + -81 -3n = 0 + -81 Combine like terms: 0 + -81 = -81 -3n = -81 Divide each side by '-3'. n = 27 Simplifying n = 27
| 0.9-x=1 | | x^3+18x^2+71x+40=0 | | u^2-u-7=0 | | -14=7x | | -15=-5x | | 4X^3-18X^2+16X+3=0 | | -8=x+12 | | 20+8q=-42 | | 21+x=-9 | | -16=x+25 | | x-7.9=3.8 | | 2(x+6)=4x-6 | | n^4+2n^3-n^2-2n=0 | | a-7=-3 | | -7-6=21-2x | | 240=22r+r^2 | | 3(x+5)=x+25 | | 5x+7=x+23 | | 5x+10=8x-11 | | 1000a+(663)=919a | | 2+b=8 | | (3x-5)[2]=19 | | 150+.50n=255 | | 5(4z-1)-2(Z+2)=14(Z+1) | | 2(x+8)-x=2(3-x)-7 | | (5x+1)[2]=7 | | (3x+1)(x+2)=-1 | | 3(5x+4)+5x=-8x | | 3x+6x=4x+9x | | 42x+37x^2-72x=46 | | x^2+10x+21=40 | | x+(x+34)=35 |